Neck-Tongue Syndrome: An Underrecognized Childhood Onset Cephalalgia. (April 2018) - Allen, Nicholas M.; Dafsari, Hormos S.; Wraige, Elizabeth; Jungbluth, Heinz
Neck-tongue syndrome is a rarely reported headache disorder characterized by occipital and/or upper neck pain triggered by sudden rotatory head movement and accompanied by abnormal sensation and/or posture of the ipsilateral tongue. Although onset is thought to be in childhood, most of the limited number of cases reported so far were adults. Here the authors describe 3 cases, 2 girls and 1 boy, with neck-tongue syndrome. In each child additional headache symptoms occurred, headache improved over time in all, spontaneously in 2 and coinciding with gabapentin treatment in the other. Investigations were consistently unremarkable. Review of the literature reveals a usually self-limiting disorder, with early onset and variable additional features. Awareness of neck-tongue syndrome among pediatric neurologists and other practitioners is important, to allow for timely diagnosis and informed management of an underreported headache disorder with childhood onset.